PEMAHAMAN PEMILIH TENTANG PASANGAN CALON PEMILIHAN PRESIDEN TAHUN 2024 Studi Pemahaman Pemilih Gen Z terhadap Pasangan Calon Presiden dalam Pemilu 2024 di Kota Padang Kota Padang - Winada, Kharisma; Damsar, Damsar; Alfiandi, Bob (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study explores Generation Z voters’ understanding and motives toward presidential candidates in the 2024 election in Padang City, against the backdrop of state intervention issues and the popularity of Prabowo-Gibran’s “gemoy” social media strategy. A qualitative approach was applied using a critical paradigm and Habermas’s hermeneutic analysis, involving 14 Gen Z informants. Findings reveal that candidate pair 01 voters are mainly highly educated individuals driven by rational motives, pair 02 voters are predominantly first-time voters influenced by their environment and the "gemoy" campaign on TikTok, while pair 03 voters critically evaluate candidates’ track records. The "gemoy" strategy created distorted political communication, shifting the focus from leadership substance to entertainment politics, yet effectively influenced Gen Z electoral decisions through social media. This phenomenon underscores the importance of political and media literacy to prevent political manipulation and promote more substantial democratic awareness among young voters.